Edukacyjne walory gry "Minecraft". Analiza narracji uczniów i edukatorów - Dorota Zaworska-Nikoniuk (Problemy Wczesnej Edukacji)
This paper shows the educational aspects of video game Minecraft in primary education. It is based on a systematic review and interviews conducted with fourteen players of the aforementioned game as well as an analysis of interviews with the creator of Young Programmer Academy and an educator of an IT class. The statements of users (players) and educators point to the potential uses of the game in learning and acquiring social skills. In the game, students create their own worlds, develop their imagination and spatial thinking, gain knowledge about the basics of technology, physics and chemistry, as well as enrich their knowledge about nature. Probably for those reasons the game is popular in Norwegian and Swedish schools, where units based on Minecraft are often incorporated by teachers into their lessons.